Our Results of Laparoscopic Partial Nephrectomies Without Pedicle Dissection: Possible Advantages and Disadvantages - Verit, Ayhan; Urkmez, Ahmet; Yuksel, Ozgur Haki; Uruc, Fatih (Urology Journal, 2019)
Purpose: This study aimed to document the surgical and oncologic results of nephron sparing of non-ischemic laparoscopic partial nephrectomy without the step of hilus controlling and even without dissecting to expose the main renal vascularity and directly focusing on mass removal. Materials & Methods: The records of the patients who underwent our modified laparoscopic partial nephrectomy technique were evaluated retrospectively. The patients’ medical records, including tumor complexity calculated via R.E.N.A.L nephrometry scores, operation time, estimated blood loss, blood transfusions, hospital stay, pre- and postoperative serum creatinine levels, complications via the Clavien classification system, pathological status of surgical margin, and follow-up times, were documented. Result: The data of 55 patients with 58 renal units were evaluated. Almost all tumors were in the low complex group (91%), with a mean size of 31.74 ± 7.38 mm (range: 12-46 mm). Mean operation time, estimated blood loss, and transfusion rates were 138.62 ± 38.45 minutes (range: 90-240 min), 242.24 ± 107.12 mL (range: 100-500 mL), and 19%, respectively. The hemoglobin level decreased by a mean of 2.05 ± 0.87 g/dL. Whereas the perioperative complications were Clavien grades I, II, and III (74%, 23%, and 3%, respectively), mean hospital stay and follow-up time were 4.05 ± 1.97 and 19.67 ± 13.57 (ranges: 2-10 days and 1-44 months), respectively. Conclusion: Present un-controlled results pointed that tumor-focusing nephron-sparing non-ischemic partial laparoscopic nephrectomy may be preferable for small-sized, low-complex renal masses.